2012
DOI: 10.5194/hessd-9-10365-2012
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Regionalised spatiotemporal rainfall and temperature models for flood studies in the Basque Country, Spain

Abstract: A spatial-temporal point process model of rainfall is fitted to data taken from three homogeneous regions in the Basque Country, Spain. The model is the superposition of two spatial-temporal Neyman-Scott processes, in which rain cells are modelled as discs with radii that follow exponential distributions. In addition, the model includes a parameter for the radius of storm discs, so that rain only occurs when both a cell and a storm disc overlap a point. The model is fitted to data for each month, taken … Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
4
0

Year Published

2016
2016
2016
2016

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(4 citation statements)
references
References 27 publications
0
4
0
Order By: Relevance
“…Rodríguez-Iturbe et al (1987a, b) developed the stochastic point process model in a way to better characterize and describe the precipitation process at the event level. Implementations of the stochastic point process models for spatio-temporal precipitation seem to work satisfactorily at temporal resolutions down to 1 h (Cowpertwait and O'Connell, 1997;Cowpertwait, 2006;Burton et al, 2008Burton et al, , 2010aCowpertwait et al, 2013). Also, downscaling to finer resolution than 1 h is inherently problematic as the scaling properties change below this point (Nguyen et al, 2002;Molnar and Burlando, 2008).…”
mentioning
confidence: 99%
See 3 more Smart Citations
“…Rodríguez-Iturbe et al (1987a, b) developed the stochastic point process model in a way to better characterize and describe the precipitation process at the event level. Implementations of the stochastic point process models for spatio-temporal precipitation seem to work satisfactorily at temporal resolutions down to 1 h (Cowpertwait and O'Connell, 1997;Cowpertwait, 2006;Burton et al, 2008Burton et al, , 2010aCowpertwait et al, 2013). Also, downscaling to finer resolution than 1 h is inherently problematic as the scaling properties change below this point (Nguyen et al, 2002;Molnar and Burlando, 2008).…”
mentioning
confidence: 99%
“…At the daily level, the Neyman-Scott rectangular pulses (NSRP) and the spatio-temporal Neyman-Scott rectangular pulses (STNSRP) models (Burton et al, 2008(Burton et al, , 2010aCowpertwait et al, 2013) have shown good skill in downscaling point precipitation extremes. This applies for individual gauges (Sunyer et al, 2012) as well as for spatially averaged precipitation covering large areas considered to have a uniform climate described by relatively few gauges (e.g.…”
mentioning
confidence: 99%
See 2 more Smart Citations